The effects of pedometer-based exercise on central and peripheral vascular functions among young sedentary men with CVD risk factors - Omar, Norsuhana; Yeoh, Boon Seng; Chellappan, Kalaivani; Chui, Sara Zijiun; Salamt, Norizam; Aminuddin, Amilia (Frontiers in Physiology, 2023)
Introduction: Cardiovascular disease (CVD) remains the main cause of morbidity and mortality in Malaysia and worldwide. This is mainly due to increase in the prevalent of CVD risk factors such as hypertension, dyslipidemia, smoking and obesity. Increased physical activity has been recommended as a modality to improve CVD risk. Pulse wave velocity (PWVCF), augmentation index (AI) and finger photoplethysmography fitness index (PPGF) have been introduced to assess the vascular functions related to CVD risk factors. The effects of long-term exercise on PPGF are not established. Materials and Methods: A total of 70 young men who were sedentary with 2 or more cardiovascular risk factors were recruited. Subjects were randomly assigned to a control group (CG) (n=34; no change in walking) and pedometer group (PG) (n=36; minimum target: 8,000 steps/day). PWVCF and AI were measured via Vicorder System. The PPGF was obtained via finger photoplethysmography method. All parameter was measured at baseline and after six and 12 weeks. Results: After intervention, the PG had significant increased step count from 4996±805 to 10,128 ±511 steps/day (P<0.001). The PG showed significant improvement in anthropometric variables, lipid, PWVCF, AI and PPGF (time and group effect p<0.001). No changes were seen in CG. Conclusion: This signify that pedometer-based walking programme is beneficial in improving markers of vascular function among young working sedentary men with CVD risk factors. Pedometer based exercise should be encouraged to improve cardiovascular health.